2016
DOI: 10.1097/md.0000000000004549
|View full text |Cite
|
Sign up to set email alerts
|

Layer-specific analysis of dobutamine stress echocardiography for the evaluation of coronary artery disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
12
0
4
Order By: Relevance
“…Rumbinaitė et al 11 found that longitudinal strain had the best predictive value for significant coronary artery stenosis (sensitivity = 89.4%, specificity = 64.7%). Park et al 12 found that GLPSS at stress has 85% sensitivity, 92% specificity, 80% PPV and 94% NPV in predicting significant CAD. In contrast, DSE was found to have 48% sensitivity, 83% specificity, 52% PPV and 81% NPV.…”
Section: Discussionmentioning
confidence: 99%
“…Rumbinaitė et al 11 found that longitudinal strain had the best predictive value for significant coronary artery stenosis (sensitivity = 89.4%, specificity = 64.7%). Park et al 12 found that GLPSS at stress has 85% sensitivity, 92% specificity, 80% PPV and 94% NPV in predicting significant CAD. In contrast, DSE was found to have 48% sensitivity, 83% specificity, 52% PPV and 81% NPV.…”
Section: Discussionmentioning
confidence: 99%
“…But recently LS2D-STE was used to predict the severity of coronary lesions. [40,41] To the best of our knowledge, this study is the first to predict VM using layer-specific strain and strain rate measured by LS2D-STE in patients with AMI. Our study showed that:…”
Section: Discussionmentioning
confidence: 99%
“…to monitor cardiotoxicity in chemotherapy patients 9 , it is still mostly used for research purposes. Recently, clinical scientists increasingly utilize STE during functional assessments such as dobutamine stress echocardiography 19 or ergometer stress testing in adult 20 and pediatric patient populations 21 . However, the reproducibility of these combinatory assessments is still largely unknown, and data is scarce or incomplete in children 22 .…”
Section: Discussionmentioning
confidence: 99%